Protect nuclear plant fasteners from boric acid corrosion - MOISIDIS, N; POPESCU, M; RATIU, M (Power engineering (Barrington, Ill.), 1992)
Boric acid corrosion of pump and valve fasteners in pressurized water reactor (PWR) power plants can be prevented by implementing appropriate fastener steel replacement and extended inspections to detect and correct the cause of leakage. A three-phase corrosion protection program based on system operability, outage-related accessibility, and cost of fastener replacement versus maintenance frequency is presented. Selection criteria for fastener material are also presented. Because of the configuration of the bolted connections, leakage at some closures is inevitable in long-term service. Therefore the replacement of carbon or low-alloy steel fasteners exposed to boric acid corrosion from leaking borated coolant with alternate material resistant to corrosion is desirable.